Clinical characteristics of critically ill patients co-infected with SARS-CoV-2 and the influenza virus in Wuhan, China. (July 2020) - Ma, Simin; Lai, Xiaoquan; Chen, Zhe; Tu, Shenghao; Qin, Kai
Highlights: A high proportion of COVID-19 patients were co-infected with influenza in Tongji Hospital (Wuhan). Critically ill COVID-19 patients with influenza were more prone to cardiac injury than those without influenza. Co-infection with the influenza virus may induce an earlier and more frequently occurring cytokine storm in critically ill COVID-19 patients. Do not ignore detection of the influenza virus in patients with COVID-19. Abstract: Objective: To delineate the clinical characteristics of critically ill COVID-19 patients co-infected with influenza. Methods: This study included adult patients with laboratory-confirmed COVID-19 form Tongji Hospital (Wuhan, China), with or without influenza, and compared their clinical characteristics. Results: Among 93 patients, 44 died and 49 were discharged. Forty-four (47.3%) were infected with influenza virus A and two (2.2%) with influenza virus B. Twenty-two (50.0%) of the non-survivors and 24 (49.0%) of the survivors were infected with the influenza virus. Critically ill COVID-19 patients with influenza were more prone to cardiac injury than those without influenza. For the laboratory indicators at admission the following were higher in non-survivors with influenza than in those without influenza: white blood cell counts, neutrophil counts, levels of tumor necrosis factor-α, D-dimer value, and proportion of elevated creatinine. Conclusion: The results showed that a high proportion of COVID-19 patients were co-infected with influenza in Tongji Hospital, with no significant difference in the proportion of co-infection between survivors and non-survivors. The critically ill COVID-19 patients with influenza exhibited more severe inflammation and organ injury, indicating that co-infection with the influenza virus may induce an earlier and more frequently occurring cytokine storm.